Does Entrepreneurship Education Really Work? A Review and Methodological Critique of the Empirical Literature on the Effects of University‐Based Entrepreneurship Education. (13th June 2013) - Rideout, Elaine C.; Gray, Denis O.; Vozikis, George; Solomon, George; Winkel, Doan
<x xml:space="preserve">Abstract</x> Does entrepreneurship education (E‐ed) really work to create business enterprise? We conducted a comprehensive review and methodological critique of the empirical research on the outcomes of university‐based E‐ed. We identified every empirical study conducted over the past decade, and found 12 that minimally met our methodologically "robust" (Storey Steps 4–6) standard. Our systematic critique of the studies' research methods found a variety of methodological weaknesses, undermining confidence in the belief that E‐ed can produce entrepreneurship. The implications for both practice and policy are discussed, and recommendations are made for conducting future E‐ed outcome research.